KONDISI FISIK RUMAH (JENIS DINDING, JENIS LANTAI, PENCAHAYAAN, KELEMBABAN, VENTILASI, SUHU, DAN KEPADATAN HUNIAN) MEMPENGARUHI KEJADIAN PENYAKIT TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS KRIAN SIDOARJO TAHUN 2021 - Adinda Mega Putri; Imam Thohari; Ernita Sari (GEMA LINGKUNGAN KESEHATAN, 2022)
Pulmonary Tuberculosis is a direct infectious disease caused by TB bacteria (Mycobacterium tuberculosis). In the Krian Health Center Work Area, the number of pulmonary TB patients has increased every year. Based on the profile of the Krian Health Center, Tuberculosis data for the last 3 years in 2017 - 2019 has increased with a percentage of 15% - 56.5% of cases. The purpose of the study was to analyze the relationship between the physical condition of the house and the incidence of pulmonary tuberculosis (TB) in the working area of the Krian Health Center in 2021.This type of research is analytic with a case control approach. Collecting data using observation sheets. The research variable is the physical condition of the house including the types of walls, floors, lighting, humidity, ventilation, temperature and density of residential dwellings with a total sample of 47 patients and 47 non-patients using purposive sampling method. The data were analyzed using the chi-square test to determine the relationship.The value of the test results from the chi square of X2 statistical test results obtained p value = 0.037, then Ha is rejected. It can be concluded that the respondent's house category is related to the incidence of pulmonary TB disease but the odd ratio calculation is obtained a value of 2,424 (CI: 1,047 – 5,611), so respondents who have a house category are quite at risk of pulmonary TB disease 2,424 times greater than respondents with a house category that is good.It is recommended for health workers to increase their role as motivators and counselors for the community in order to increase knowledge about the importance of the physical condition of houses that meet the requirements for health by scheduling periodic counseling about healthy homes.